An Analysis of English Pronunciation Errors by Sunset Eyewear Employees in Bali, Indonesia - Meyke Laura M; I Wayan Budiarta; I Wayan I Wayan Ana (Journal of Comprehensive Science, 2026)
This research examines English pronunciation errors produced by Indonesian employees at Sunset Eyewear, Bali, during workplace communication. The aim of this research is to identify the types of pronunciation errors and to explain the factors influencing them. The analysis is grounded in Selinker’s Interlanguage Theory (1972), which emphasizes the role of first language influence in second language production. A descriptive qualitative method was employed. Data were collected through audio recordings of natural workplace interactions and were transcribed using the International Phonetic Alphabet (IPA). The analysis was supported by the SpeechAce application (version 1.3.2) to ensure phonetic accuracy. In addition, semi-structured interviews were conducted to explore the factors underlying the errors. The findings indicate that the most frequent errors include sound substitution, voicing errors, and final consonant devoicing, such as /?/ ? /t/, /ð/ ? /d/, and /z/ ? /s/. These errors are influenced by interconnected factors, including first language interference, educational background, workplace communication demands, shifting communicative goals, and limited phonological awareness. It is concluded that targeted pronunciation practice and greater exposure to accurate spoken English are needed to improve clarity and effectiveness in workplace communication